1995
DOI: 10.1128/jcm.33.12.3290-3295.1995
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial outbreak caused by Scedosporium prolificans (inflatum): four fatal cases in leukemic patients

Abstract: Four cases of fatal disseminated Scedosporium prolificans (inflatum) infection occurring in neutropenic patients are reported. Because of hospital renovation, the patients were cared for in a temporary hematologic facility. S. prolificans (inflatum) was isolated from blood cultures of these four patients, two of whom underwent full necropsy, and revealed abundant vegetative hyphae and ovoid conidia with truncate bases in many organs. In vitro susceptibility testing of fungal strains showed all isolates to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…Although many of the published cases have come from Australia and Spain, cases have also been reported in other European countries and the Americas. A second series reported four cases of fatal infection occurring in patients with recently diagnosed leukaemia [6]. All four patients were neutropenic and had rapid development of respiratory symptoms in association with pulmonary in®ltrates on chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Although many of the published cases have come from Australia and Spain, cases have also been reported in other European countries and the Americas. A second series reported four cases of fatal infection occurring in patients with recently diagnosed leukaemia [6]. All four patients were neutropenic and had rapid development of respiratory symptoms in association with pulmonary in®ltrates on chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Localized infections of immunocompetent individuals by S. prolificans are rare (Greig et al, 2001), but disseminated infections of immunocompromised patients are increasing in frequency and now account for approximately 25% of all non-Aspergillus mould infections in organ transplant recipients (Husain et al, 2003). The fungus causes debilitating diseases in a broad spectrum of patients at risk for invasive fungal infections including AIDS patients (Hopwood et al, 1995), allogeneic bone marrow and solid organ transplant recipients (Lionakis et al, 2004;Vagefi et al, 2005;Bouchara et al, 2009;Pihet et al, 2009a), and patients with neutropenia, acute lymphoblastic leukaemia and haematological malignancies (Alvarez et al, 1995;Maertens et al, 2000;Song et al, 2009). In neutropenic cancer patients and transplant recipients, disseminated infections are rapid (Alvarez et al, 1995;Husain et al, 2003;Marco de Lucas et al, 2006), with mortality rates of up to 75-80% (Rodriguez-Tudela et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The fungus causes debilitating diseases in a broad spectrum of patients at risk for invasive fungal infections including AIDS patients (Hopwood et al, 1995), allogeneic bone marrow and solid organ transplant recipients (Lionakis et al, 2004;Vagefi et al, 2005;Bouchara et al, 2009;Pihet et al, 2009a), and patients with neutropenia, acute lymphoblastic leukaemia and haematological malignancies (Alvarez et al, 1995;Maertens et al, 2000;Song et al, 2009). In neutropenic cancer patients and transplant recipients, disseminated infections are rapid (Alvarez et al, 1995;Husain et al, 2003;Marco de Lucas et al, 2006), with mortality rates of up to 75-80% (Rodriguez-Tudela et al, 2009). Along with the closely related fungi Pseudallescheria boydii and S. apiospermum, S. prolificans is recovered from the sputum samples of cystic fibrosis patients, but its involvement in disease aggravation has yet to be determined (Bouchara et al, 2009;Pihet et al, 2009a;Harun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…6,27,28 A number of outbreak reports suggest that commencing antifungal prophylaxis during an outbreak may also be of benefit. 9,11,27,[29][30][31] However, most of these reports came from outbreaks that occurred before 1995 when antifungal prophylaxis for high-risk patient groups was not yet routine. We recommend lowering the threshold for antifungal prophylaxisusing a broader-spectrum antifungal agent or including patient groups other than those at 'high' risk -in the presence of ongoing building works.…”
Section: Outbreak Managementmentioning
confidence: 99%
“…have also been linked to building works. 1,11 A small, retrospective, case-control study revealed that IFI 'cases' confirmed at autopsy were more likely to have been hospitalized during hospital construction work (P < 0.02). 10 A separate clinico-epidemiological study found that rates of IFI rose from 1.2% pre-construction to 7.9% when construction was at its peak (P < 0.001).…”
mentioning
confidence: 99%